Propuesta de mejoramiento de la tecnología asistida como recurso didáctico en la educación de estudiantes con discapacidad en el Instituto Fiscal de Discapacidad Motriz “INSFIDIM” durante el año lectivo 2015-2016 - Villegas López, Sara Verónica (2016)
The systematization of the project "Assistive technology as a teaching resource in the education of children with motor disabilities was held at the Institute on Disability Attorney Motive" Insfidim "during the 2015-2016 school year. The project was developed with the aim to optimize student learning, similarly to publicize the benefit of the application of assistive technology in the classroom as a teaching resource that provides access to information and communication. According to these parameters, the main achievement obtained through the analysis and reflection of the experience of the application of ICT, was to make more efficient use of the tool by registering valuable experiences that provided in the teaching process student-learning. The proposed use of assistive technology to indicate the level of use of technology in the classroom. Was achieved also promote innovations developed from the experience, which will be feasible for application in other educational institutions that serve students with disabilities, thus supporting the social and educational inclusion of this population